Magnetic memory in nanocrystalline α-Fe2O3 embedded in reduced graphene oxide. Issue 99 (24th September 2015) - Sarkar, S.; Mondal, A.; Dey, K.; Ray, R.
Abstract : Single phase iron oxide (α-Fe2 O3 ) of nearly regular ellipsoidal shape, embedded in reduced graphene oxide (RGO) has been prepared by the chemical route. Memory effect is observed in magnetization study. Abstract : Single phase iron oxide (α-Fe2 O3 ) of nearly regular ellipsoidal shape, embedded in reduced graphene oxide (RGO) has been prepared by the chemical route. In the chemical synthesis, a modified Hummers's method is used to prepare graphene oxide (GO). The reduction of GO to RGO is carried out using hydrazine hydrate. Interestingly, X-ray diffraction (XRD), high resolution Transmission Electron Microscopy (TEM), X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared (FTIR) spectroscopy confirm α-Fe2 O3 without evidence of trace amounts of Fe3 O4 . The results point out that the oxide phase of Fe i.e., α-Fe2 O3 does not undergo any reduction process. Structural, morphological and spectroscopic characterizations have been performed by XRD, FESEM, TEM and XPS studies. Investigation of dc magnetization studies at low temperatures and low magnetic fields infer, super spin glass (SSG) behavior as manifested through relaxation dynamics and zero field cooled (ZFC) magnetic memory effects.